Enhancing the Quality of Geography Teaching. An Explorative Study Evaluating the Effectiveness of Ready-to-Use Teaching Resources - Golay, David; Rempfler, Armin; Vettiger, Barbara (Journal of Geography Education, 2012)
Using an explorative multi-phase study we tried to explore the effectiveness of so called 'Basic Modules' in teaching. These teaching modules have been created for a range of geographical topics and contain theory-based curriculum making ideas as well as subject knowledge resources. We argue that teachers using these modules are better enabled to consider pedagogical ideas in their teaching practice than those who do not. The evaluation study of the 'Basic Modules' is based on one hand on a qualitative enquiry (interrogation) of geography teachers who taught one of the 'Basic Modules' and on the other hand on a quantitative study designed to scrutinize student's learning achievements and their attitudes towards the new teaching method/'Basic Modules'. Moreover, the study explores to which extent the concept of learning presented by the 'Basic Module' has been accepted by the teachers and how much it had been effecting their own teaching. As a result, a first set of hypothesis about the quality of geography education from year 7 to 9 might be tested. Taking into account the small and less representative data base, we could nevertheless observe that teachers rather preferred to focus on the subject knowledge resources of the 'Basic Modules' than on dealing with the theoretical concepts.
Keywords: Subject oriented study in teaching-quality-research, multi-phase study, geography based criteria for measuring quality of geography teaching, perceptions of teaching, explorative pilot study